2010
DOI: 10.1136/thx.2010.138990
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin in the treatment of asthma: lack of steroid-sparing effect

Abstract: Background Statins have anti-inflammatory actions which in theory are potentially beneficial in asthma. Small trials have failed to show a significant benefit, but a systematic study to evaluate the steroid-sparing effect of statin treatment has not been carried out. Methods A randomised, placebo-controlled, crossover trial was conducted of simvastatin 40 mg at night with simultaneous stepwise reduction of fluticasone propionate dose until loss of control occurred, followed by an increase until regain of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 37 publications
(49 reference statements)
1
69
3
1
Order By: Relevance
“…11,17,19,20 There was no significant heterogeneity among the four trials before ( 2 ¼ 1.29, I 2 ¼ 0%; Figure 1) and after ( 2 ¼ 0.38, I 2 ¼ 0%; Figure 2) ICS. Compared with the control group, the FEV 1 of the statin group was 0.09 l (95% CI À0.06, 0.23) higher before ICS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…11,17,19,20 There was no significant heterogeneity among the four trials before ( 2 ¼ 1.29, I 2 ¼ 0%; Figure 1) and after ( 2 ¼ 0.38, I 2 ¼ 0%; Figure 2) ICS. Compared with the control group, the FEV 1 of the statin group was 0.09 l (95% CI À0.06, 0.23) higher before ICS.…”
Section: Resultsmentioning
confidence: 99%
“…There were three trials with a crossover study design. 11,19,20 Two trials compared atorvastatin with placebo 11,20 and two compared simvastatin with placebo. 17,19 Characteristics of the included trials are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations